Surgical drainage of spontaneous sublingual haematoma. Issue 6 (9th June 2022) - Hamilton, Amanda; Beardsley, Christian
Abstract : This is a case presentation of a man in his late 80s who presented to emergency department with a sublingual haematoma secondary to warfarin usage for atrial fibrillation. His international normalised ratio was rapidly reversed, and he was taken to theatre for successful surgical drainage of the haematoma. He was kept intubated and ventilated for 48 hours postoperatively to allow swelling to settle then extubated and rehabilitated prior to discharge home.